A New Gallery of the Art of the Ancient East - Terrace, Edward L. В.
Achaemenid relief with attacking bull, bronze disc, relief from Persepolis, Assyrian relief with soldiers (palace of Sennacherib at Nineveh), timber and statuette of an Assyrian king, head of Gudea, Early Dyn. III cylinder seal, Akkadian cylinder seal of hunt, Neobabylonian cylinder seal, Luristan bronze, coup from Persia, painted bowl with birds, small objects.